Efektivitas Model Pembelajaran Berbasis HOTS dalam Meningkatkan Kemampuan Analisis Siswa di MI Negeri 36 Bireuen - Nurmasyitah, Nurmasyitah; Nurmiati, Nurmiati; Irofah, Nurma (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
In the era of globalization, higher order thinking skills (HOTS) are essential competencies for students. HOTS includes analysis, evaluation, and creation skills that enable students to solve problems critically and creatively. However, observations at MIN 36 Bireuen show that students' analytical skills are still low, where they tend to just memorize without understanding the concepts deeply. One solution that can be applied is a HOTS-based learning model, which challenges students with problem-solving tasks and analysis-based discussions. This study aims to evaluate the effectiveness of HOTS model in improving students' analytical skills through Classroom Action Research (PTK) method. The research was conducted in two cycles involving planning, implementation, observation, and reflection. Data were collected through observations, interviews, and analysis tests before and after the application of the HOTS learning model. The results showed that this model significantly improved students' analytical thinking ability, learning motivation, as well as their social skills in working together. Thus, HOTS-based learning model is recommended as an effective strategy to improve learning quality in MIN 36 Bireuen and other schools.